Can Manifest Destiny Justify the Ruckus on the Klamath River Basin? A Detailed Study of Settler Colonialism on Klamath Tribes (Global Journal of Human-Social Science, 2019)
The headlines of contemporary news articles render the following "Fish Blood in their veins, fewer Salmon in their river," "Removal of Klamath Dams would be the largest River Restoration in U S History,", and "Will the Klamath River Salmon survive after the dams are gone?".A closer look into these heated discussions helps us understand that all is not well on the Klamath River Basin. Although dams and low salmon runs feature among the current debates, water allocation remains the crux of the issue. These issuesmake us question the why and how of water distribution among the populace that sustains on the Klamath Basin and how power plays an important role in water allocation. The Klamath River, the life blood of indigenous communities is virtually connected to their identity, culture, spirituality and thereby sovereignty. This research paper probes into this issue on the Klamath Basin over land and water resources and help us define how changing patterns of Settler Colonialism has invaded Tribal Sovereignty in the twentieth century.
Keywords: klamath river; settler colonialism; tribal sovereignty; salmon kills; klamath dams